Studies on bacteria able to use methane in denitrification - Davies, Trevor Rodney (Department of Molecular and Cell Biology, 2016)
The aim of this investigation was to determine the suitability of single carbon organic compounds as hydrogen donors for denitrification. Although methanol has been used for this purpose with some success, methane has apparently been disregarded as a possible carbon source. A denitrifying unit was operated with methanol as a carbon source, in order to determine the influence of methanol on rates of denitrification with several different nitrate concentrations. With methanol as an additive, nitrate reduction was of the order of 90%, while less than 40% denitrification was achieved with the supernatant from settled domestic sewage as the sole carbon source. Isolates were taken from this unit for identification. A similar unit was constructed, receiving methane as the sole carbon source. Bacteria were isolated from this unit and shown to be able to use nitrate as a terminal electron acceptor and as a source of cell nitrogen. These bacteria were identified and their specificity to methane tested. In addition to methane they were found to be able to use several other organic compounds for growth and denitrification. Isolates from the methanol unit were found to be able to use methane for denitrification.